Effect of Pandemic COVID-19 on Tropical Forest Cover in Small Island: Case Mansinam Island Papua using Google Earth Imagery - Hematang, Francine; Taran, Denisa; Mutakim; Erari, Semuel; Luas, Alfando; Worabai, Descarlo; Matheus Beljai (Jurnal Manajemen Hutan Tropika, 2025)
Covid-19 became a global pandemic in 2020 and has multiple impacts on the economy, social, culture, food systems, and also the environment, especially on tropical forest cover in small island. This study aims to determine the impact of the Covid-19 pandemic on the forest cover of small populated islands. Using remote sensing and geographic information system technology based on high-resolution satellite imagery from google earth imagery, land cover was observed in 2018, 2020, and 2023. This study found that during the 2020 pandemic, tropical forest cover on small populated islands has decreased. Mansinam's forest cover decreased by 4.3%, bare land increased by 80.6%, agricultural land increased by 75.3%, and shrubs increased by 54.9%. Another important finding is that 78.9% of the total deforestation was due to forest conversion to bare land and agricultural land. Land and forest utilization on small islands will increase when accessibility is limited, especially during the pandemic. Future studies will be on the structure and composition of species in locations that experienced deforestation during the pandemic and detailed studies related to changes in the occupations of Mansinam people due to the pandemic that have a relationship with forests.